Discerning asthma endotypes through comorbidity mapping - Gengjie Jia; Xue Zhong; Hae Kyung Im; Nathan Schoettler; Milton Pividori; D. Kyle Hogarth; Anne I. Sperling; Steven R. White; Edward T. Naureckas; Christopher S. Lyttle; Chikashi Terao; Yoichiro Kamatani; et al. (Nature Communications, 2022)
Asthma is a heterogeneous, complex syndrome that arises in individuals with various genetic and exposure variations. Here, the authors show that disease comorbidity patterns can serve as a surrogate for these variations, and identify asthma endotypes distinguished by comorbidity patterns, asthma risk loci, gene expression, and health-related phenotypes.